On-Going European Space Agency Activities on Measuring the Benefits of Earth Observations to Society: Challenges, Achievements and Next Steps - Tassa, Alessandra; Willekens, Stephanie; Lahcen, Arne; Laurich, Laurent; Mathieu, Charlotte (Frontiers in Environmental Science, 2022)
Understanding the Earth system and its physical and societal processes is crucial to help humankind to develop in a sustainable way and to design effective policies across a wide range of applications that include the mitigation of the effects of climate change, the sustainable management of natural resources, food security and public health. Earth observation (EO) satellites provide regular and accurate observations of the entire planet that can greatly support improvements in such understanding. The European Space Agency is committed to support international efforts to decipher the processes and phenomena that regulate life on Earth, by building world class EO space missions and making data available to scientists and citizens worldwide. How successful is the Agency in such endeavor? Given the variable and dynamic nature of EO data use, the question can hardly be answered through established figures. Yet, the capability to discern the benefits brought by the use of its EO missions is crucial for ESA to demonstrate its achievements, to ever improve its systems as well as to promote further uptake. In this article, after recalling its commitments in support to Earth system sciences, ESA’s attempts to conduct valuations of the impact of its own space missions are described. In particular, the challenges encountered in measuring such impacts and the solutions pursued by the Agency to improve its assessment capabilities are detailed, together with the open issues and the current lines of work.